Ultra-high strength titanium alloy spring for rail transit and preparation method thereof
Patent Information
- Application Number
- CN202611175091.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-20
AI Technical Summary
从现有工程应用来看,当前轨道交通用高强钛合金弹簧通常是通过添加铝铌合金引入Nb元素,利用Nb元素的固溶强化作用提升合金强度,但该类合金室温抗拉强度不足1250 MPa,难以满足超高强钛合金室温抗拉强度≥1300 MPa的性能要求
1)本申请提供的轨道交通用超高强钛合金弹簧具有良好的外观形状、表面质量和力学性能,产品使用寿命长,适合大批量生产,对拓展低成本、超高强钛合金弹簧制件应用市场具有重要意义。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This application belongs to the field of powder metallurgy technology, and specifically relates to an ultra-high strength titanium alloy spring for rail transit and its preparation method. Background Technology
[0002] Springs for rail transit are core vibration damping components in vehicle bogie systems, playing a crucial role in connection, positioning, and vibration damping during vehicle operation. As an important part of the vehicle suspension system, springs must simultaneously withstand dynamic loads in three directions between the spring seat and the frame, and effectively mitigate bogie vibration amplitude through their own vibration characteristics, thus significantly impacting vehicle stability, comfort, and safety. Titanium alloys, with their advantages of low density, high specific strength, and good corrosion and heat resistance, have been increasingly applied in the rail transit field. They can effectively reduce the weight of vehicle suspension systems, increase train speed, extend the service life of vehicle components and tracks, and reduce vehicle maintenance frequency. However, traditional titanium alloy springs for rail transit typically involve preparing ingots through three vacuum arc melting processes, followed by multi-stage forging and rolling. This process suffers from high raw material costs, complex procedures, and a tendency to cause component segregation. Furthermore, the room temperature tensile strength of the produced spring components is below 1300 MPa, severely limiting its application.
[0003] To address the demand for low-cost, short-process, and high-performance titanium alloy springs, a powder metallurgy approach is proposed: composition customization is achieved through element mixing, effectively reducing raw material costs and suppressing component segregation; simultaneously, micro-alloying enhances alloy strength. In terms of forming technology, cold isostatic pressing is employed, avoiding the complex processes of repeated melting, multi-stage forging, and multi-pass rolling in traditional methods, significantly shortening the manufacturing process and reducing production costs. Current engineering applications show that high-strength titanium alloy springs for rail transit typically introduce Nb by adding aluminum-niobium alloys, utilizing Nb's solid solution strengthening effect to improve alloy strength. However, the room temperature tensile strength of such alloys is less than 1250 MPa, failing to meet the performance requirement of ultra-high-strength titanium alloys with a room temperature tensile strength ≥1300 MPa. Summary of the Invention
[0004] The purpose of this application is to provide an ultra-high strength titanium alloy spring for rail transit and its preparation method. The ultra-high strength titanium alloy spring for rail transit in this application has a multi-level heterogeneous synergistic effect α-phase composite structure, which includes serrated grain boundary α-phase and micron-scale lamellar α-phase. L Phase and ultrafine crystalline nano α sThis multi-scale, multi-morphological α-phase composite material enables low-cost manufacturing of ultra-high-strength titanium alloy spring components for rail transit. Furthermore, through interphase deformation coordination and heterogeneous deformation-induced strengthening effects, the final spring sample exhibits a room-temperature tensile strength ≥1600 MPa, an elongation ≥8%, and a fatigue life exceeding 2 million cycles under 440 MPa stress, overcoming the technical challenge of synergistically improving the strength and fatigue performance of traditional high-strength titanium alloys.
[0005] The first aspect of this application provides an ultra-high strength titanium alloy spring for rail transit, wherein the ultra-high strength titanium alloy spring has a multi-level heterogeneous composite structure composed of a β-transformation matrix and multiple α-phase configurations; the multiple α-phase configurations include serrated grain boundary α-phase, micron-scale lamellar α-phase, etc. L Phase and ultrafine crystalline nano α s The morphology of the serrated grain boundary α phase exhibits continuous convex and concave features, with local curvature continuously changing along the interface length direction; the micron-scale lamellar α phase... L Phase with the ultrafine crystalline nano α s The phase is dispersed within the β-transformation matrix, and each of the ultrafine crystalline nano α phases is dispersed within the matrix. s The phases are arranged in an alternating pattern.
[0006] In some embodiments of this application, the micron-scale sheet α L The phase length ranges from 0.83 μm to 4.77 μm, and the aspect ratio ranges from 1.43 to 3.67.
[0007] In some embodiments of this application, the ultrafine crystalline nano α s The phase width ranges from 53 nm to 137 nm.
[0008] In some embodiments of this application, the width of the serrated grain boundary α phase is 70 nm to 120 nm.
[0009] In some embodiments of this application, the ultra-high strength titanium alloy spring has a room temperature tensile strength ≥1600MPa and an elongation ≥8%.
[0010] In some embodiments of this application, the ultra-high strength titanium alloy spring has a fatigue life of more than 2 million cycles under a stress of 440 MPa.
[0011] The second aspect of this application provides a method for preparing the ultra-high strength titanium alloy spring for rail transit as described in the first aspect, comprising the following steps: subjecting a mixed powder containing hydrogenated dehydrogenated titanium-based powder and alloy element powder to cold isostatic pressing to obtain a powder compact; wherein the alloy element powder includes Zr powder; subjecting the powder compact to vacuum sintering to obtain a sintered compact; subjecting the sintered compact to multi-stage forging in a high-temperature β single-phase region to obtain a spring preform; subjecting the spring preform to hot rolling, solution treatment, aging treatment, and hot coiling treatment in sequence to obtain the ultra-high strength titanium alloy spring.
[0012] In some embodiments of this application, the hydrogenated dehydrogenated titanium-based powder includes both hydrogenated dehydrogenated titanium alloy powder and hydrogenated dehydrogenated titanium powder.
[0013] In some embodiments of this application, the alloy element powder also includes elemental powders of Mo, V, and Cr.
[0014] In some embodiments of this application, the oxygen content of the hydrogenated dehydrogenated titanium-based powder is ≤2700 ppm and the particle size is ≤40 μm.
[0015] In some embodiments of this application, the oxygen content of the alloy element powder is ≤3000 ppm and the particle size is ≤38 μm.
[0016] In some embodiments of this application, the holding pressure of the cold isostatic pressing treatment is 150 MPa to 300 MPa, and the holding time is 5 min to 30 min.
[0017] In some embodiments of this application, the vacuum sintering includes: heating the powder compact to a first sintering temperature at a first heating rate, then heating it to a second sintering temperature at a second heating rate, holding it at that temperature, and then naturally furnace cooling it to 700°C~850°C; subsequently, introducing inert gas and air cooling it to 50°C~100°C.
[0018] In some embodiments of this application, the first heating rate is 2°C / min to 10°C / min.
[0019] In some embodiments of this application, the first sintering temperature is preferably 1000℃~1100℃.
[0020] In some embodiments of this application, the second heating rate is 2°C / min to 5°C / min.
[0021] In some embodiments of this application, the second sintering temperature is 1100℃~1350℃, and the holding time is 3h~7h.
[0022] In some embodiments of this application, the vacuum sintering is performed under a vacuum atmosphere with a vacuum level lower than 1×10⁻⁶. -3 Pa.
[0023] In some embodiments of this application, the temperature of each forging stage is 850°C to 1050°C.
[0024] In some embodiments of this application, the multi-fire forging includes single-fire forging, double-fire forging, triple-fire forging and quadruple-fire forging, wherein the deformation amount of the single-fire forging is not less than 7.5%.
[0025] In some embodiments of this application, the total forging deformation of the sintered billet is ≥30%.
[0026] In some embodiments of this application, the solution treatment temperature is 700℃~820℃, and the holding time is 0.5 h~2 h.
[0027] In some embodiments of this application, the heating rate of the solution treatment is 2°C / min to 6°C / min.
[0028] In some embodiments of this application, the temperature of the hot rolling process is 900°C to 1000°C.
[0029] In some embodiments of this application, the hot rolling process is performed by continuous multi-pass rolling with a final rolling temperature ≥750°C.
[0030] In some embodiments of this application, the aging treatment temperature is 400℃~650℃, and the holding time is 4h~8h.
[0031] In some embodiments of this application, the heating rate of the aging treatment is 2°C / min to 6°C / min.
[0032] In some embodiments of this application, the temperature of the hot coil spring treatment is 800°C to 900°C.
[0033] In some embodiments of this application, the preparation method further includes at least one of the following treatments on the spring preform: grinding, peeling, length setting, cold straightening, and polishing.
[0034] This application has the following advantages: 1) The ultra-high strength titanium alloy spring for rail transit provided in this application has good appearance, surface quality and mechanical properties, long service life and is suitable for mass production. It is of great significance for expanding the application market of low-cost, ultra-high strength titanium alloy spring parts.
[0035] 2) The composition is customized by using hydrogenated dehydrogenated Ti-6Al-4V powder combined with trace element powder. The alloy strength is improved by Zr micro-alloying solid solution strengthening, while reducing raw material costs and composition segregation tendency.
[0036] 3) The powder blank is forged in the high temperature β single phase region in four heats. The high temperature and multiple deformations effectively refine the grains and control the phase distribution, providing distortion energy for the nucleation of heterogeneous structures.
[0037] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are given below. Attached Figure Description
[0038] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0039] Figure 1 These are microstructure images of ultra-high strength titanium alloy spring parts obtained after solution aging treatment according to some embodiments of this application; wherein, Figure 1 (a) in the figure is a microstructure diagram of the alloy; Figure 1 (b) in the middle is Figure 1 Enlarged view of the local microstructure in (a) of the image; Figure 2 The images shown are physical representations of ultra-high strength titanium alloy spring components according to some embodiments of this application. Detailed Implementation
[0040] Exemplary embodiments of this application will now be described in more detail with reference to the accompanying drawings. While exemplary embodiments of this application are shown in the drawings, it should be understood that this application may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of this application and to fully convey the scope of this application to those skilled in the art.
[0041] It should be understood that the terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “described” as used herein may also include the plural forms. The terms “comprising,” “including,” “containing,” and “having” are inclusive and therefore indicate the presence of the stated features, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components, and / or combinations thereof. The method steps, processes, and operations described herein are not construed as requiring them to be performed in a particular order described or illustrated unless the order of performance is explicitly indicated. It should also be understood that additional or alternative steps may be used.
[0042] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0043] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0044] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0045] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0046] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0047] The first aspect of this application provides an ultra-high strength titanium alloy spring for rail transit, combined with... Figure 1 The ultra-high strength titanium alloy spring is described as having a multi-level heterogeneous composite structure composed of a β-transformation matrix and various α-phase configurations; the various α-phase configurations include serrated grain boundary α-phase and micron-scale lamellar α-phase. L Phase and ultrafine crystalline nano α s The morphology of the α phase with serrated grain boundaries exhibits continuous convex and concave features, with local curvature continuously changing along the length of the interface; micron-scale lamellar α phase L Phase and ultrafine crystalline nano α s The phase is dispersed within the β-transformation matrix, with each ultrafine crystalline nano-α phase dispersed within the matrix. s The phases are arranged in an alternating pattern.
[0048] In the embodiments of this application, the ultra-high strength titanium alloy spring for rail transit has a multi-level heterogeneous synergistic effect α-phase composite structure. The α-phase at the grain boundaries of this structure has a serrated morphology, which helps to alleviate grain boundary stress concentration; simultaneously, micron-scale lamellar α-phase precipitates within the grains. L Phase and ultrafine crystalline nano α s The phases constitute intralayer heterogeneous units with alternating soft and hard phases. This multi-scale, multi-morphological α-phase composite, through interphase deformation coordination and heterogeneous deformation-induced strengthening effect, enables the final spring sample to achieve a room temperature tensile strength ≥1600MPa, an elongation ≥8%, and a fatigue life exceeding 2 million cycles under 440 MPa stress, breaking through the technical challenge of synergistically improving the strength and fatigue performance of traditional high-strength titanium alloys.
[0049] In some embodiments of this application, micron-scale sheets α L The phase lengths range from 0.83 μm to 4.77 μm, with aspect ratios ranging from 1.43 to 3.67. As an example, micron-scale α-sheets... L The phase length can be one of 0.83 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 4.77 μm, or any value satisfying the above range. As an example, a micrometer-scale α-sheet... LThe aspect ratio of the phase can be one of 1.43, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.2, 2.4, 2.5, 2.8, 3, 3.2, 3.5, 3.6, 3.67 or any value that satisfies the above range.
[0050] In some embodiments of this application, ultrafine crystalline nano α s The phase width ranges from 53 nm to 137 nm. As an example, ultrafine-grained nano-α... s The width of the phase can be one of 53 nm, 55 nm, 58 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, 132 nm, 135 nm, 137 nm or any value that satisfies the above range.
[0051] In some embodiments of this application, the width of the serrated grain boundary α phase is 70 nm to 120 nm. As an example, the width of the serrated grain boundary α phase can be one of 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm or any value satisfying the above range.
[0052] In some embodiments of this application, the ultra-high strength titanium alloy spring has a room temperature tensile strength ≥1600 MPa and an elongation ≥8%.
[0053] In some embodiments of this application, the ultra-high strength titanium alloy spring has a fatigue life of more than 2 million cycles under a stress of 440 MPa.
[0054] The second aspect of this application provides a method for preparing an ultra-high strength titanium alloy spring for rail transit, thereby obtaining the ultra-high strength titanium alloy spring for rail transit described in the first aspect of this application.
[0055] In the embodiments of this application, a Zr element microalloying solid solution strengthening strategy is proposed. This strategy further enhances alloy strength through customized Zr element composition and combines it with high-temperature β-single-phase hot forging technology to achieve low-cost manufacturing of ultra-high-strength titanium alloy spring components. The preparation method first involves adding Zr to prepare powder with a customized composition. A combination of cold isostatic pressing and vacuum sintering is then used to obtain a high-density, uniformly structured titanium alloy sintered billet. Next, a titanium alloy spring preform is prepared through high-temperature β-single-phase hot forging. Finally, through solid solution aging treatment, a multi-level heterogeneous synergistic α-phase composite microstructure is designed, which includes serrated grain boundary α-phase and micron-scale lamellar α-phase. L Phase and ultrafine crystalline nano α sThis enables the low-cost manufacturing of ultra-high strength titanium alloy spring components for rail transit.
[0056] In some embodiments of this application, the preparation method of ultra-high strength titanium alloy springs for rail transit is mainly carried out according to the following steps.
[0057] (1) The mixed powder containing hydrogenated dehydrogenated titanium-based powder and alloy element powder is subjected to cold isostatic pressing to obtain powder compact.
[0058] In the embodiments of this application, the mixed powder is customized by combining hydrogenated dehydrogenated titanium-based powder (hydrogenated dehydrogenated Ti-6Al-4V powder) with alloy element powder (trace element powder) to improve the alloy strength and improve the composition uniformity. Subsequently, a titanium alloy sintered billet with high density and uniform structure is prepared by using a process combining cold isostatic pressing and vacuum sintering.
[0059] Specifically, the preparation process of powder compact mainly includes the following steps: (1-1) Raw material preparation In the embodiments of this application, the hydrogenated dehydrogenated titanium-based powder includes two types: hydrogenated dehydrogenated titanium alloy powder and hydrogenated dehydrogenated titanium powder.
[0060] In the embodiments of this application, the oxygen content of the hydrogenated dehydrogenated titanium-based powder is ≤2700 ppm and the particle size is ≤40 μm.
[0061] In the embodiments of this application, the alloying element powder includes four types of powder: Mo powder, V powder, Cr powder, and Zr powder.
[0062] In the embodiments of this application, the oxygen content of the alloy element powder is ≤3000 ppm and the particle size is ≤38 μm.
[0063] In the embodiments of this application, hydrogenated dehydrogenated Ti-6Al-4V powder, hydrogenated dehydrogenated Ti powder, Mo powder, V powder, Cr powder, and Zr powder are selected as raw material powders.
[0064] (1-2) Mixed powder In the embodiments of this application, the raw material powder prepared in step (1-1) is loaded into a mixing bottle, placed on a mixer for mixing, and then sieved after mixing.
[0065] In the embodiments of this application, the ratio of each raw material powder is Ti-5Al-5Mo-5V-3Cr-1Zr (wt.%).
[0066] In the embodiments of this application, the mixing process parameters for hydrogenated dehydrogenated titanium-based powder and alloy element powder include: a rotation speed of 150 r / min to 200 r / min, rotating forward for 30 min and stopping for 5 min, then rotating backward for 30 min and stopping for 5 min, with a total mixing time of 6 h to 10 h. As an example, the rotation speed can be one of 150 r / min, 160 r / min, 170 r / min, 175 r / min, 180 r / min, 190 r / min, 200 r / min, or any value within the above range. As an example, the total mixing time can be one of 6 h, 7 h, 8 h, 9 h, 10 h, or any value within the above range.
[0067] In the embodiments of this application, the mixing bottle has a capacity of 2 L.
[0068] In the embodiments of this application, the oxygen content of the hydrogenated dehydrogenated Ti-6Al-4V powder is less than 2100 ppm and the particle size is ≤30 μm.
[0069] In the embodiments of this application, the oxygen content of the hydrogenated dehydrogenated Ti powder is less than 2700 ppm and the particle size is ≤40 μm.
[0070] In the embodiments of this application, the oxygen content of the Mo powder is less than 3000 ppm and the particle size is ≤10 μm.
[0071] In the embodiments of this application, the oxygen content of V powder is less than 3000 ppm and the particle size is ≤10 μm.
[0072] In the embodiments of this application, the oxygen content of the Cr powder is less than 1500 ppm and the particle size is 1 μm to 3 μm.
[0073] In the embodiments of this application, the oxygen content of the Zr powder is less than 2000 ppm and the particle size is ≤38 μm.
[0074] (1-3) Packaging In the embodiments of this application, the sieved mixed powder is filled into a sleeve and then compacted by vibration.
[0075] In the embodiments of this application, the sheath is made of materials such as rubber or silicone, and the shrinkage rate of the sheath is 30% to 40% of the size of the powder compact. As an example, the shrinkage rate of the sheath can be one of 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, or 40%, or any value that meets the above range.
[0076] (1-4) Blank preparation In the embodiments of this application, a cold isostatic pressing process is used to prepare powder compacts.
[0077] In embodiments of this application, the cold isostatic pressing process parameters include: a holding pressure of 150 MPa to 300 MPa and a holding time of 5 min to 30 min. As an example, the holding pressure for cold isostatic pressing can be one of 150 MPa, 160 MPa, 170 MPa, 180 MPa, 190 MPa, 200 MPa, 210 MPa, 220 MPa, 230 MPa, 240 MPa, 250 MPa, 260 MPa, 270 MPa, 280 MPa, 290 MPa, or 300 MPa, or any value satisfying the above range. The holding time can be one of the following: 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, or any value within the above range.
[0078] (2) Vacuum sintering In the embodiments of this application, the powder compact is vacuum sintered to obtain a sintered compact.
[0079] Specifically, the powder compact can be placed in a vacuum sintering furnace for vacuum sintering to obtain a powder sintered compact.
[0080] In some embodiments of this application, vacuum sintering includes heating the powder compact to a first sintering temperature at a first heating rate, then heating it to a second sintering temperature at a second heating rate, holding it at that temperature, and then naturally furnace cooling it to 700°C~850°C; subsequently, inert gas is introduced for air cooling to 50°C~100°C. As an example, the temperature is held at that temperature and then naturally furnace cooled to one of 700°C, 750°C, 780°C, 790°C, 800°C, 810°C, 820°C, or 850°C, or any value within the above range.
[0081] In some embodiments of this application, the first heating rate is 2°C / min to 10°C / min. As an example, the first heating rate can be one of 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any value satisfying the above range.
[0082] In some embodiments of this application, the first sintering temperature is 1000℃~1100℃. As an example, the first sintering temperature can be one of 1000℃, 1040℃, 1050℃, 1060℃, 1080℃, 1100℃ or any value that satisfies the above range.
[0083] In some embodiments of this application, the second heating rate is 2°C / min to 5°C / min. As an example, the second heating rate can be one of 2°C / min, 3°C / min, 4°C / min, 5°C / min, or any value satisfying the above range.
[0084] In some embodiments of this application, the second sintering temperature is 1100℃~1350℃, and the holding time is 3 h~7 h. As an example, the second sintering temperature can be one of 1100℃, 1150℃, 1200℃, 1250℃, 1280℃, 1300℃, and 1350℃, or any value satisfying the above range. As an example, the holding time can be one of 3 h, 4 h, 5 h, 6 h, and 7 h, or any value satisfying the above range.
[0085] In some embodiments of this application, vacuum sintering is performed under vacuum or a protective atmosphere.
[0086] In the embodiments of this application, vacuum sintering is performed under vacuum (vacuum degree less than 1×10⁻⁶). -3 The sintering process is carried out under a protective atmosphere of argon (purity ≥99.999%) or inert gas (purity ≥99.999%). The specific sintering process includes: heating the powder compact prepared by cold isostatic pressing from room temperature to 1000℃~1100℃ at a heating rate of 2℃ / min~10℃ / min; then heating it to 1100℃~1350℃ at a heating rate of 2℃ / min~5℃ / min and holding it for 3 h~7 h; after the sintering process is completed, naturally cooling it in a furnace to 700℃~850℃; then air cooling it with inert gas to 50℃~100℃, and a titanium alloy sintered compact with high density and uniform structure can be obtained.
[0087] It is worth mentioning that "room temperature" in the embodiments of this application generally refers to a state without active heating and cooling. Generally speaking, the room temperature is typically between 20°C and 35°C, for example, it can be one of 20°C, 25°C, 28°C, 30°C, or 35°C, or any value that meets the above range.
[0088] (3) The sintered billet is forged in the high-temperature β single-phase region through multiple forging processes to obtain the spring preform.
[0089] In embodiments of this application, multi-stage forging includes single-stage forging, double-stage forging, triple-stage forging, and quadruple-stage forging, wherein the temperature of each forging stage is 850°C to 1050°C. As an example, the temperature of each forging stage can be one of 850°C, 900°C, 950°C, 1000°C, 1020°C, or 1050°C, or any value satisfying the above range.
[0090] In some embodiments of this application, the preparation of the spring preform mainly includes the following steps: (3-1) One-time forging In some embodiments of this application, the sintered billet is first placed in an atmosphere-protected furnace, heated to the forging temperature and held for a period of time; then the sintered billet after the holding period is subjected to a single forging (first forging) deformation, and then returned to the furnace.
[0091] In some embodiments of this application, the deformation amount of the first forging (single-fire forging) is not less than 7.5%. As an example, the deformation amount of the single-fire forging can be one of 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 11%, or any value that satisfies the above range.
[0092] In some embodiments of this application, the forging temperature is 850℃~1050℃, and the holding time is 10 min~40 min. As an example, the forging temperature can be one of 850℃, 890℃, 900℃, 910℃, 950℃, 960℃, 980℃, 1000℃, 1020℃, and 1050℃, or any value satisfying the above range. As an example, the holding time can be one of 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, and 40 min, or any value satisfying the above range.
[0093] (3-2) Two-stage forging Repeat step (3-1).
[0094] In some embodiments of this application, the deformation amount of the two-stage forging is not less than 8%. As an example, the deformation amount of the two-stage forging can be one of 8%, 8.5%, 9%, 9.5%, 10%, 11%, or any value that satisfies the above range.
[0095] (3-3) Three-stage forging Repeat step (3-1).
[0096] In some embodiments of this application, the deformation amount of three-stage forging is not less than 8%. As an example, the deformation amount of two-stage forging can be one of 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, or any value that satisfies the above range.
[0097] (3-4) Fourth-stage forging Repeat step (3-1), that is, perform a fourth forging deformation on the billet, and finally let it cool naturally in the air to room temperature.
[0098] In some embodiments of this application, the deformation amount of four-stage forging is not less than 8%. As an example, the deformation amount of two-stage forging can be one of 8%, 8.5%, 8.8%, 9%, 9.5%, 10%, 10.5%, 11%, or any value that satisfies the above range.
[0099] In some embodiments of this application, after the fourth forging is completed, the total forging deformation of the sintered billet reaches more than 30%, and a spring preform is obtained.
[0100] In some embodiments of this application, the dimensions of the spring preform include: a diameter of 100 mm and a length of not less than 350 mm.
[0101] (4) The spring preform is subjected to hot rolling, solution treatment, aging treatment and hot coiling treatment in sequence to obtain ultra-high strength titanium alloy spring.
[0102] In this application embodiment, a method for preparing ultra-high strength titanium alloy spring parts by four-stage forging in the high-temperature β single-phase region is provided by customizing the alloy composition. This method reduces costs, shortens the process flow, and produces ultra-high strength titanium alloy spring parts with good appearance, surface quality, and mechanical properties. The products have a long service life and are suitable for mass production. This method is of great significance for expanding the application market for low-cost, ultra-high strength titanium alloy spring parts.
[0103] In the embodiments of this application, the ultra-high strength titanium alloy spring has a multi-level heterogeneous synergistic α-phase composite structure, which includes serrated grain boundary α-phase and micron-scale lamellar α-phase. L Phase and ultrafine crystalline nano α s Mutually.
[0104] Specifically, the ultra-high strength titanium alloy springs for rail transit have a composite microstructure consisting of a β-transformation matrix and multiple α-phase configurations with a multi-level heterogeneous synergistic effect; the multiple α-phase configurations include serrated grain boundary α-phase and micron-scale lamellar α-phase. L Phase and ultrafine crystalline nano α sPhases. Among them, the serrated grain boundary α phase forms along the original β grain boundary, with a morphology featuring continuous protrusions and depressions, and continuous changes in local curvature. The width of the serrated grain boundary α phase is approximately 70 nm to 120 nm; micron-scale lamellar α... L Phase with a large number of interwoven ultrafine crystalline nano α s The phase is uniformly precipitated within the β-transformation matrix, with micron-scale α-sheets. L Phase lengths range from approximately 0.83 μm to 4.77 μm, with aspect ratios of 1.43 to 3.67; ultrafine-grained nano-α s The phase width is approximately 53 nm to 137 nm.
[0105] In some embodiments of this application, the preparation of ultra-high strength titanium alloy springs mainly includes the following steps: (4-1) Grinding In the embodiments of this application, the oxide scale, cracks and other defects on the surface of the above-mentioned spring preform are cleaned by grinding.
[0106] In some embodiments of this application, the edges of the grinding portion are rounded for a smooth transition, and the depth-to-width ratio of the grinding defect portion is no greater than 1:6. For example, the depth-to-width ratio of the grinding defect portion can be one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6 or any value that satisfies the above range.
[0107] (4-2) Hot rolling In the embodiments of this application, the spring preform after grinding is heated to the hot rolling temperature, held at that temperature for a period of time, and then rolled out of the furnace.
[0108] In some embodiments of this application, the hot rolling temperature is 900°C to 1000°C. As an example, the hot rolling temperature can be one of 900°C, 920°C, 950°C, 980°C, and 1000°C, or any value satisfying the above range.
[0109] In some embodiments of this application, hot rolling involves loading the spring preform into an electric resistance furnace at a temperature of ≤700°C, heating it to 900°C~1000°C, holding it at that temperature for 1 h~4 h, and then rolling it out of the furnace.
[0110] In some embodiments of this application, hot rolling is performed using continuous multi-pass rolling, wherein the temperature of the first rolling pass is 900°C to 1000°C, and the final rolling temperature of the last rolling pass is ≥750°C.
[0111] In some embodiments of this application, after three rolling passes, the diameter of the spring preform is reduced from 100 mm to 16 mm, and the final rolling temperature is ≥750℃.
[0112] (4-3) Peeling and cutting to length In the embodiments of this application, the oxide layer on the surface of the spring preform obtained after hot rolling is removed, and the uneven parts at both ends of the spring preform are cut off to obtain the required length.
[0113] In some embodiments of this application, the diameter of the processed spring preform is 12 mm to 13 mm.
[0114] In some embodiments of this application, defective positions at both ends of the spring preform are removed, and the length of the spring preform after sawing is controlled between 3350 mm and 3380 mm, and the final length after flattening is ensured to be 3350 mm + 10 mm.
[0115] (4-4) Solution treatment In the embodiments of this application, the spring preform obtained after peeling and length setting is placed in an atmosphere protection furnace, heated to the solution temperature, held at the temperature for a period of time, and then air-cooled.
[0116] In some embodiments of this application, the solution treatment temperature is 700℃~820℃, and the holding time is 0.5 h~2 h. As an example, the solution treatment temperature can be one of 700℃, 720℃, 750℃, 780℃, 790℃, 800℃, 810℃, or 820℃, or any value satisfying the above range. As an example, the holding time can be one of 0.5 h, 0.8 h, 1 h, 1.2 h, 1.5 h, 1.8 h, or 2 h, or any value satisfying the above range.
[0117] In some embodiments of this application, the heating rate of the solution treatment is 2°C / min to 6°C / min. As an example, the heating rate of the solution treatment can be one of 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, or any value satisfying the above range.
[0118] In some embodiments of this application, the solution treatment involves heating the spring preform from room temperature to 700°C to 820°C at a heating rate of 2°C / min to 6°C / min, and holding it at that temperature for 0.5 h to 2 h.
[0119] (4-5) Timeliness processing In the embodiments of this application, the spring preform obtained after solution treatment is placed in an atmosphere-protected furnace, heated to the aging temperature, held at that temperature for a certain time, and then air-cooled.
[0120] In some embodiments of this application, the aging treatment temperature is 400℃~650℃, and the holding time is 4 h~8 h. As an example, the aging treatment temperature can be one of 400℃, 420℃, 450℃, 480℃, 500℃, 520℃, 550℃, 580℃, 600℃, 620℃, or 650℃, or any value satisfying the above range. As an example, the holding time can be one of 4 h, 5 h, 6 h, 7 h, or 8 h, or any value satisfying the above range.
[0121] In some embodiments of this application, the heating rate of the aging treatment is 2℃ / min to 6℃ / min. As an example, the heating rate of the aging treatment can be one of 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, or any value satisfying the above range.
[0122] In some embodiments of this application, the aging treatment involves heating the spring preform obtained from the solution treatment from room temperature to 400°C to 650°C at a heating rate of 2°C / min to 6°C / min, and holding it at that temperature for 4 h to 8 h, so that the room temperature tensile strength of the spring part reaches more than 1600 MPa and the elongation reaches more than 8.0%, which meets the requirements of the room temperature mechanical properties of ultra-high strength titanium alloy.
[0123] (4-6) Cold straightening, grinding and polishing In the embodiments of this application, the spring preform obtained after aging treatment is straightened, and then ground and polished to ensure the precision and smoothness of the blank surface.
[0124] In some embodiments of this application, the straightness of the spring preform after straightening is ≤1 mm / m.
[0125] In some embodiments of this application, the dimensions of the spring preform after grinding and polishing are controlled to be 12.5 mm in diameter, 1 m in length, and a diameter tolerance of ±0.05 mm.
[0126] (4-7) Coil Spring In the embodiments of this application, the spring preform obtained after cold straightening and polishing is hot-rolled to obtain the spring part.
[0127] In some embodiments of this application, the coil spring is hot-rolled, and the hot-rolling temperature is controlled between 800°C and 900°C. As an example, the hot-rolling spring temperature can be one of 800°C, 820°C, 850°C, 880°C, and 900°C, or any value that satisfies the above range.
[0128] (4-8) Sandblasting In the embodiments of this application, the surface of the spring component after coil spring processing is sandblasted to obtain an ultra-high strength titanium alloy spring component.
[0129] In some embodiments of this application, 100-mesh quartz sand is used for sandblasting, and the sandblasting time is not less than 10 minutes per piece.
[0130] In some embodiments of this application, after spraying, the missed areas are manually sandblasted until the sandblasting coverage reaches 100%, and finally the ultra-high strength titanium alloy spring parts are obtained.
[0131] In the embodiments of this application, the finished ultra-high strength titanium alloy spring is a titanium alloy forging for rail transit. This titanium alloy forging has a multi-level heterogeneous synergistic effect α-phase composite structure, which includes serrated grain boundary α phase and micron-scale lamellar α phase. L Phase and ultrafine crystalline nano α s Mutually.
[0132] In the embodiments of this application, the addition of Zr plays a crucial role in the formation of a multi-level heterogeneous composite structure. During the solid solution stage, because the diffusion rate of Zr atoms is lower than that of Ti atoms, Zr atoms accumulate in the liquid phase at the solid-liquid interface, forming a compositionally supercooled region. This expands the nucleation driving force, promotes the formation of more grains, effectively refines the original β grains, provides denser nucleation sites for the subsequent precipitation of the α phase, and, in conjunction with forging deformation, facilitates the formation of serrated grain boundary α phase. Simultaneously, the addition of Zr causes the solid solution to expand, resulting in severe lattice distortion, introducing an inhomogeneous strain field and compositional fluctuations, promoting the formation of a large number of ultrafine nanocrystalline α phases during aging. s The phase is dispersed and uniformly precipitated. Therefore, by combining customized trace element powder composition, vacuum sintering, four-stage forging in the high-temperature β single-phase region, and solution aging, it is possible to obtain ultra-high-strength titanium alloy spring parts with excellent room-temperature mechanical properties. The density of this ultra-high-strength titanium alloy spring part is close to 100%, and its room-temperature mechanical properties and fatigue performance far exceed those of traditional forgings.
[0133] In some embodiments of this application, a low-cost, ultra-high-strength titanium alloy spring component for rail transit is disclosed, which mainly includes the following steps: (1) Preparation of customized mixed powder with added alloying element powder (trace element powder) by element mixing method: Based on the actual production needs of existing springs, Zr element was selected as the micro-alloying solid solution strengthening element. The nominal ratio was calculated according to the type and content of the required trace alloying elements. Hydrogenated dehydrogenated Ti-6Al-4V powder, hydrogenated dehydrogenated Ti powder, Mo powder, V powder, Cr powder, and Zr powder were used as raw material powders and mixed uniformly. The mixing process parameters were: rotation speed 150 r / min~200 r / min, forward rotation for 30 min, stop for 5 min, then reverse rotation for 30 min, stop for 5 min, and the total mixing time was 6 h~10 h.
[0134] (2) Preparation of titanium alloy sintered billets by vacuum sintering: The mixed titanium alloy powder is loaded into a silicone sleeve and cold isostatically pressed. The holding pressure is 150 MPa to 300 MPa, and the holding time is 5 min to 30 min. The titanium alloy powder billet obtained by cold isostatic pressing is placed in a vacuum sintering furnace and heated to 1000℃ to 1100℃ at a heating rate of 2℃ / min to 10℃ / min, and then heated to 1100℃ to 1350℃ at a heating rate of 2℃ / min to 5℃ / min, and held for 3 h to 7 h. After the sintering process is completed, the furnace is naturally cooled to 700℃ to 850℃, and then inert gas is introduced for air cooling to 50℃ to 100℃, to obtain titanium alloy sintered billets with a density of over 99%.
[0135] (3) Preparation of titanium alloy spring preforms by four-stage forging in the high-temperature β single-phase region: The above-mentioned titanium alloy sintered billet was placed in an atmosphere-protected furnace and heated to 850℃~1050℃. After holding at this temperature for 10 min~40 min, the first forging was performed, with a deformation of ≥7.5%. The above forging steps were then repeated twice. Finally, the titanium alloy billet was heated to 850℃~1050℃ and held at this temperature for 10 min~40 min, followed by a fourth forging. After completion, it was air-cooled to room temperature. After four-stage forging, the total forging deformation of the titanium alloy sintered billet reached more than 30%, forming a titanium alloy spring preform. The preform has a diameter of 100 mm and a length of not less than 350 mm.
[0136] (4) Solution treatment and aging to prepare ultra-high strength titanium alloy spring parts: The above-mentioned titanium alloy spring preform is ground, and the edges and corners of the ground parts are rounded and the depth-to-width ratio of the ground defect parts is not greater than 1:6. Then the preform is loaded into the furnace at ≤700℃, heated to 900℃~1000℃, held for 1 h~4 h and then rolled. After three rollings, the diameter of the billet is reduced to 16mm and the final rolling temperature is ≥750℃. Then the oxide layer on the surface of the titanium alloy is removed by peeling, and the diameter of the billet after processing is 12 mm~13mm. The defects at both ends of the billet are removed, and the length of the billet after sawing is controlled between 3350 mm~3380 mm. The final length after flattening is 3350 mm+10 mm. The fixed-length billet is placed in an atmosphere protection furnace for solution treatment, heated from room temperature to 700℃~820℃ at a heating rate of 2℃ / min~6℃ / min, held for 0.5 h~2 h, and then air-cooled. Following this, an aging treatment was performed, heating the spring from room temperature to 400℃~650℃ at a heating rate of 2℃ / min~6℃ / min, holding for 4 h~8 h, and then air cooling. After solution aging treatment, the room temperature tensile strength of the spring part was ≥1600 MPa, and the elongation was ≥8.0%, meeting the room temperature mechanical property requirements of ultra-high strength titanium alloys. Cold straightening was then performed, with a straightness ≤1 mm / m after straightening. The bar stock was then ground and polished to ensure surface precision and smoothness. The dimensions of the processed billet were 12.5 mm in diameter, 1 m in length, and a diameter tolerance of ±0.05 mm. The billet was then heated to 800℃~900℃ to complete hot rolling. The spring part was sandblasted using 100-mesh quartz sand for ≥10 min per piece, with manual re-sandblasting of any missed areas to ensure 100% sandblasting coverage. This resulted in a low-cost, ultra-high strength titanium alloy spring part.
[0137] Unless otherwise defined, the technical terms used in the following embodiments have the same meaning as commonly understood by those skilled in the art to which this application pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are all conventional biochemical reagents; the raw materials, instruments, and equipment used in the following embodiments can all be obtained through commercial purchase or by existing methods; the amounts of experimental reagents used are, unless otherwise specified, the amounts used in conventional experimental operations; and the experimental methods used are, unless otherwise specified, conventional methods. It should be further noted that the following descriptions are merely exemplary and not intended to limit the scope of this application. Moreover, the comparative examples below are selected to compare with the technical solutions of this application to demonstrate the advancement of the technical solutions of this application, and do not necessarily represent prior art in this technical field.
[0138] Example 1 Based on the actual production needs of existing springs, Zr was selected as the microalloying solid solution strengthening element. The nominal proportions of the required trace alloying elements were calculated according to their types and contents. Hydrogenated dehydrogenated Ti-6Al-4V powder, hydrogenated dehydrogenated Ti powder, Mo powder, V powder, Cr powder, and Zr powder were used as raw materials and uniformly mixed. The mixing process parameters were: rotation speed 175 r / min, forward rotation for 30 min, stop for 5 min, then reverse rotation for 30 min, stop for 5 min, for a total mixing time of 8 h.
[0139] The mixed titanium alloy powder was loaded into a silicone mold and cold isostatically pressed at a pressure of 250 MPa for 10 min. The resulting titanium alloy powder compact was then placed in a vacuum sintering furnace and heated to 1100°C at a rate of 5°C / min, followed by a heating rate of 2°C / min to 1300°C, and held at that temperature for 5 h. After the sintering process was completed, the furnace was allowed to cool naturally to 800°C, followed by air cooling with inert gas to 50°C, resulting in a titanium alloy sintered compact with a density of 99.1%.
[0140] The titanium alloy sintered billet was heated to 950°C in a protective atmosphere furnace and held for 30 minutes before the first forging, resulting in a deformation of 7.5%. This forging process was then repeated twice. Finally, the titanium alloy billet was heated to 950°C, held for 30 minutes, and then forged a fourth time, followed by air cooling to room temperature. After four forging cycles, the total forging deformation of the titanium alloy sintered billet reached 30%, forming a titanium alloy spring preform. The preform has a diameter of 100 mm and a length of 400 mm.
[0141] The aforementioned titanium alloy spring preform was ground, with rounded edges and a depth-to-width ratio of no more than 1:6 for the ground areas. The preform was then loaded into a furnace at 700℃, heated to 96℃, held for 3 hours, and then rolled. After three rolling passes, the billet diameter was reduced to 16 mm, with a final rolling temperature of 780℃. The oxide layer on the titanium alloy surface was then removed, resulting in a billet diameter of 12.5 mm. Defects at both ends were then removed, and the billet length was sawn to 3380 mm, with a final length of 3360 mm after flattening. The sized billet was then placed in an atmosphere-protected furnace for solution treatment, heated from room temperature to 800℃ at a rate of 5℃ / min, held for 2 hours, and then air-cooled. Aging treatment was then performed, heating from room temperature to 500℃ at a rate of 5℃ / min, held for 6 hours, and then air-cooled. After solution treatment and aging, the spring parts exhibit a room temperature tensile strength of 1601 MPa and an elongation of 8.0%, meeting the room temperature mechanical property requirements of ultra-high strength titanium alloys. Cold straightening was then performed, resulting in a straightness of 0.8 mm / m. The bar stock was subsequently ground and polished to ensure surface precision and smoothness. The finished billet dimensions were 12.5 mm in diameter and 1 m in length. The billet was then heated to 820℃ for hot rolling. The spring parts were then sandblasted using 100-mesh quartz sand for 10 minutes per piece, with manual touch-ups for any missed areas to ensure 100% sandblasting coverage. This process ultimately yielded low-cost, ultra-high strength titanium alloy spring parts.
[0142] Examples 2-6 The same preparation process as in Example 1 was adopted. The only differences between Examples 2 to 6 and Example 1 were: powder mixing speed, total powder mixing time, cold isostatic pressing forming pressure, holding time, sintering temperature, heating rate, sintering time, forging temperature, and solution aging treatment process parameters. The preparation process parameters of Examples 1 to 6 are summarized in Table 1.
[0143] Table 1
[0144] Comparative Example 1 The preparation process in Comparative Example 1 is the same as that in Example 1, but the difference is that the mixing speed is 100 r / min.
[0145] Comparative Example 2 The preparation process in Comparative Example 2 is the same as that in Example 1, but the difference is that the cold isostatic pressing holding pressure is 100 MPa.
[0146] Comparative Example 3 The preparation process in Comparative Example 3 is the same as that in Example 1, but the difference is that the powder compact sintering process uses atmospheric pressure sintering.
[0147] Comparative Example 4 The preparation process in Comparative Example 4 is the same as that in Example 1, but the difference is that the forging temperature is 1100°C.
[0148] Comparative Example 5 The preparation process in Comparative Example 5 is the same as that in Example 1, but the difference is that the solution temperature is 600°C and the solution is cooled by water after the heat preservation is completed.
[0149] Comparative Example 6 The preparation process in Comparative Example 6 is the same as that in Example 1, but the difference is that the aging temperature is 350°C and water cooling is performed after the heat preservation is completed.
[0150] Performance testing (1) Observation of tissue morphology The microstructure morphology of the alloy was observed using scanning electron microscopy (SEM, ZEISS).
[0151] (2) Mechanical property testing According to GB / T 228.1-2021 standard, room temperature mechanical properties were tested using a universal testing machine.
[0152] (3) Fatigue performance test The spring samples were tested using a fatigue testing machine to verify whether the titanium alloy springs met the specified fatigue characteristics. Specifically, the fatigue limit of the samples was tested under a boundary load of 440 MPa, and the samples passed the test with over 2 million cycles.
[0153] The titanium alloy spring parts prepared in Examples 1-6 and Comparative Examples 1-6 were subjected to corresponding performance tests according to the same test methods, and the test results are summarized in Table 2.
[0154] Table 2
[0155] Testing revealed that the titanium alloy spring parts prepared using the methods described in Examples 1-6 exhibited a multi-level heterogeneous synergistic α-phase composite microstructure, comprising serrated grain boundary α-phase and micron-scale lamellar α-phase. L Phase and ultrafine crystalline nano α s Phase, micron-scale α-sheet L Phase and ultrafine crystalline nano α s The phase is distributed inside the β matrix, and its room temperature mechanical properties and fatigue properties are extremely excellent, far exceeding the level of existing high-strength titanium alloy forgings.
[0156] Analysis of the test data in Table 2 shows that reducing the mixing speed in Comparative Example 1 resulted in uneven mixing of titanium alloy powder, leading to component segregation in the prepared titanium alloy spring parts and the absence of serrated grain boundary α phase.
[0157] In Comparative Example 2, reducing the cold isostatic pressing pressure resulted in more pores and a significant decrease in density in the titanium alloy powder sintered blank, leading to a significant decline in the mechanical and fatigue properties of the resulting titanium alloy spring parts.
[0158] In Comparative Example 3, atmospheric pressure sintering was used. Although argon (Ar) gas was introduced for protection during the sintering process, air still entered, causing the oxygen content of the sample to increase to a certain extent. This resulted in stress concentration at both ends of the titanium alloy spring part, a significant decrease in the elongation and fatigue performance of the material, and a low safety factor.
[0159] In Comparative Example 4, the forging temperature was maintained in the high-temperature β single-phase region, but the excessively high temperature caused the titanium alloy billet to have excessive fluidity, making the forming process difficult to control and resulting in poor surface quality of the titanium alloy spring parts.
[0160] In Comparative Example 5, lowering the solution temperature and changing the cooling method resulted in a large difference in cooling rate between the edge and the interior of the billet, leading to uneven microstructure. This resulted in significant differences in the mechanical properties of different parts of the titanium alloy spring component and large fluctuations in fatigue performance.
[0161] In Comparative Example 6, lowering the aging temperature and changing the cooling method resulted in the incomplete transformation of the brittle ω phase into the α phase in the microstructure, which had a significant impact on the mechanical and fatigue properties of the titanium alloy spring parts.
[0162] It can also be seen that any change in process parameters in this application will directly affect the performance of the powder blank and the forging process, making it impossible to obtain ultra-high strength titanium alloy spring parts with full density, uniform structure, excellent mechanical properties and fatigue performance.
[0163] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A high-strength titanium alloy spring for rail transit, characterized in that, The ultra-high strength titanium alloy spring has a multi-level heterogeneous composite structure composed of a β-transformation matrix and α phases with various configurations; The various α-phase configurations include serrated grain boundary α-phase and micron-scale lamellar α-phase. L Phase and ultrafine crystalline nano α s The morphology of the serrated grain boundary α phase exhibits continuous convex and concave features, with local curvature continuously changing along the length of the interface. The micron-scale sheet α L Phase with the ultrafine crystalline nano α s The phase is dispersed within the β-transformation matrix, and each of the ultrafine crystalline nano α phases is dispersed within the matrix. s The phases are arranged in an alternating pattern.
2. The ultra-high strength titanium alloy spring for rail transit as described in claim 1, characterized in that, The micron-scale sheet α L The phase length ranges from 0.83 μm to 4.77 μm, and the aspect ratio ranges from 1.43 to 3.
67. And / or, the ultrafine crystalline nano α s The phase width is 53 nm to 137 nm; And / or, the width of the serrated grain boundary α phase is 70 nm to 120 nm.
3. The ultra-high strength titanium alloy spring for rail transit as described in claim 1 or 2, characterized in that, The ultra-high strength titanium alloy spring has a room temperature tensile strength ≥1600 MPa and an elongation ≥8%; And / or, the ultra-high strength titanium alloy spring has a fatigue life of more than 2 million cycles under a stress of 440 MPa.
4. A method for preparing an ultra-high strength titanium alloy spring for rail transit according to any one of claims 1 to 3, characterized in that, Includes the following steps: A mixed powder comprising hydrogenated dehydrogenated titanium-based powder and alloying element powder is subjected to cold isostatic pressing to obtain a powder compact; wherein the alloying element powder includes Zr powder. The powder compact is vacuum sintered to obtain a sintered compact. The sintered billet is forged in a high-temperature β single-phase region through multiple firings to obtain a spring preform; The spring preform is subjected to hot rolling, solution treatment, aging treatment and hot coiling treatment in sequence to obtain the ultra-high strength titanium alloy spring.
5. The preparation method according to claim 1, characterized in that, The hydrogenated dehydrogenated titanium-based powder includes two types: hydrogenated dehydrogenated titanium alloy powder and hydrogenated dehydrogenated titanium powder. Preferably, the alloying element powder further includes elemental powders of Mo, V, and Cr; Preferably, the oxygen content of the hydrogenated dehydrogenated titanium-based powder is ≤2700 ppm and the particle size is ≤40 μm; Preferably, the oxygen content of the alloy element powder is ≤3000 ppm and the particle size is ≤38 μm.
6. The preparation method according to claim 1, characterized in that, The holding pressure of the cold isostatic pressing process is 150 MPa to 300 MPa, and the holding time is 5 min to 30 min. Preferably, the vacuum sintering includes: heating the powder compact to a first sintering temperature at a first heating rate, then heating to a second sintering temperature at a second heating rate, holding at the temperature, and then naturally furnace cooling to 700 ℃~850 ℃; subsequently, air cooling with inert gas to 50 ℃~100 ℃. Preferably, the first heating rate is 2℃ / min to 10℃ / min, and the first sintering temperature is preferably 1000℃ to 1100℃; preferably, the second heating rate is 2℃ / min to 5℃ / min, the second sintering temperature is preferably 1100℃ to 1350℃, and the holding time is 3 h to 7 h. Preferably, the vacuum sintering is performed under a vacuum atmosphere with a vacuum level lower than 1×10⁻⁶. -3 Pa.
7. The preparation method according to claim 1, characterized in that, The temperature for each forging stage is 850℃~1050℃; Preferably, the multi-fire forging includes single-fire forging, double-fire forging, triple-fire forging, and quadruple-fire forging, wherein the deformation amount of the single-fire forging is not less than 7.5%; Preferably, the total forging deformation of the sintered billet is ≥30%.
8. The preparation method according to claim 1, characterized in that, The solution treatment temperature is 700℃~820℃, and the holding time is 0.5 h~2 h; Preferably, the heating rate of the solution treatment is 2℃ / min to 6℃ / min; Preferably, the hot rolling temperature is 900℃~1000℃; Preferably, the hot rolling process employs continuous multi-pass rolling with a final rolling temperature ≥750℃.
9. The preparation method according to claim 1, characterized in that, The aging treatment temperature is 400℃~650℃, and the holding time is 4 h~8 h; Preferably, the heating rate of the aging treatment is 2℃ / min to 6℃ / min; Preferably, the temperature for the hot coil spring treatment is 800℃~900℃.
10. The preparation method according to claim 1, characterized in that, The preparation method further includes at least one of the following treatments on the spring preform: grinding, peeling, length setting, cold straightening, and polishing.